DEVELOPING A MODEL FOR PROMOTING ASSET BASED COMMUNITY DEVELOPMENT (ABCD) IN NIGERIA - Hanachor, M.E.; Wordu, E. N. (International Journal of Research -GRANTHAALAYAH, 2021)
Asset based community development (ABCD) is a shift and direct contrast to the conversional need-based community development (NBD). It focuses on community asset as useful tool to stir up the development of a community. It is concerned with what is available in the community that could be used to development as against dependence on outsiders or expert for development. The different types of asset in communities were enumerated. The benefits and criticisms against the approach were also highlighted. A model to guide the application of the approach was designed. The paper is of the view that every development intervention in the nation should have its root on asset-based development approach.